Predictive bioactivity of compounds from Vitis gracilis leaf extract to counteract doxorubicin-induced cardiotoxicity via sirtuin 1 and adenosine monophosphate-activated protein kinase: An in-silico study - Putra Santoso, Syafruddin Ilyas, Yurnadi Hanafi Midoen, Rita Maliza, Dinda Fadhillah Belahusna (Journal of Applied Pharmaceutical Science, 2024)
Doxorubicin is a potent chemotherapy drug. However, it is known to cause cardiotoxicity via inhibition of sirtuin 1 (SIRT1) and adenosine monophosphate protein kinase (AMPK) activity in the cardiomyocytes. This research aimed to explore the pharmacokinetics, safety, and bioactivity of compounds from Vitis gracilis leaves in their interaction with SIRT1 and AMPK to counteract doxorubicin-induced cardiotoxicity. A total of 13 selected compounds from V. gracilis leaf extract were screened for their pharmacokinetics, toxicity, and interactions with SIRT1 and AMPK using in silico approach. It was found that the majority of the compounds are easily absorbed by the human intestine, mostly avoiding liver enzyme CYP2D6 interaction and kidney protein OCT2 inhibition. They span nontoxic to harmful, some posing hepatoxic, carcinogenic, and immunotoxic risks, while 12 meet drug-likeness criteria. Finally, molecular docking revealed that several compounds exhibit high binding affinities to the proteins SIRT1 and AMPK, with some even outperforming the standard drug resveratrol such as 3’,4’-dimethoxy-alpha-naphthoflavone, 5-[6-hydroxy-5-(3-methylbut-2-enyl)-1-benzofuran-2-yl]benzene-1,3-diol, 4,4-dimethyl-5alpha-cholesta-8,14,24- trien-3beta-ol, and norethindrone acetate. Therefore, the compounds could be considered candidates of drugs to counteract doxorubicin-induced cardiotoxicity via SIRT1 and AMPK activation.
Keywords: AMPK, cancer, chemotherapy drug, doxorubicin, resveratrol, SIRT1